Land Distribution and Identification of Types of Mount Ungaran Arabica Coffee as Strengthening of Geographical Indication Protection in Ngesrepbalong Village, Limbangan, Kendal - Gustaman, Fulia Aji; Nugraha, Satya Budi; Antari Ayuning Arsi; Danang Dwi Saputro; Dhita Prasisca Mutiatari; Budiansyah, Dadan Budiansyah (Universitas Negeri Semarang, 2024)
The existence of coffee cultivation has the potential to pioneer the Geographical Indication Protection Society/Masyarakat Perlindungan Indikasi Geografis (MPIG) as an effort to increase legal protection for brands and competitive advantage. One of the positive impacts of having geographical indications is that the product has a brand image that can be identified by potential consumers in the form of information regarding the advantages and benefits of the product. The service is carried out using a participatory method involving partners as the main actors with activity steps including: 1) Socialization, 2) Participatory coffee land mapping, 3) Identification of superior Arabica coffee clones, 4) Rebranding of Endemica coffee packaging, 5) Evaluation, and 6) Mentoring. The development of geographical indications for Mount Ungaran coffee was carried out through coffee land mapping, identification of superior clones of Arabica coffee and rebranding of Endemica coffee packaging. Method used Based on the results of participatory land mapping, there are 8 blocks of coffee land with both robusta and arabica types. Meanwhile, in the identification of superior Mount Ungaran Arabica coffee, there are types of Arabica coffee clones consisting of Kartika 1, Sigarar Rutang, and Lini S 795. Meanwhile, the packaging rebranding is carried out through changes to the packaging to strengthen the identity of the Endemica coffee product.